Revitalisasi Kampung Adat di Beo Ruteng Pu’u Manggarai Nusa Tenggara Timur - Reinaldis Merciayu Parna Jeltiung; Aliffiati Aliffiati; Diaz Restu Darmawan (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2025)
Revitalization of traditional villages is one of the efforts to preserve local culture, which is now being actively promoted in various regions, including in Beo Ruteng Pu’u, Manggarai, East Nusa Tenggara. This study aims to describe the form of revitalization taking place in the traditional village of Beo Ruteng Pu’u. The theoretical framework used in this research is Anthony F.C. Wallace’s Revitalization Movement Theory, which helps to understand both the forms of revitalization. A qualitative research method was employed, with data collected through observation, in-depth interviews with traditional elders, members of the Beo Ruteng Traditional Institution, and local residents, as well as document analysis. The findings reveal that the revitalization program includes physical improvements to the traditional village, such as repairing damaged structures and constructing access roads as part of a cultural romanticism movement. Non-physical developments also accompany the physical revitalization, including the strengthening of customary values and increasing cultural knowledge among the younger generation. Overall, the revitalization in Ruteng Pu’u serves as an example of successful development based on local culture. The synergy between formal structures and traditional wisdom has made the development process more meaningful and sustainable.